Incorporating Multimedia To Enhance An Effectual Learning Inside Language Classroom - et. al., P. Preethi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Nowadays, Teachers of English Language Teaching endeavours the most innovative method of incorporating multimedia technology to enhance students’ enthusiasm, assimilate language skills and self-learning circumstance. The main goal of this research paper is to explore Language learners’ response with appropriate statistical proofs towards multimedia tools in common and its influence in enhancing accentual patterns of commonly misspelt English words in specific. It also observes the outcome of multimedia and the teacher's part in facilitating students' to acquire vocabulary easily. The statistical investigation was taken at VISTAS, Chennai, Tamilnadu, in three ways and the outcome of utilizing multimedia devices was discovered to be stupendous and engrossing.